The theme of love for 20th century Chinese women writers : the interrelation between their lives and works - Li, Yimei (2010)
与“自传写作“的重点，本研究探讨的个性和在20世纪中国女性作家的情感，并在其文学作品中的爱情故事的痕迹。它首先是一个写的自传中发展20世纪中国女性作家的概述，涉及级数分别有鲜明的特点。尤其是，“半自传“的诗学日益盛行自20世纪90年代。女性主义精神分析和由J.希利斯米勒和Deuwe Fokklema发展理论绘画，随后分别在重点章节自传张爱玲，琼瑶，三毛的著作，并在努力学习的女性作家及其作品的个性。 With focus on "autobiographic writing", this study explores the personalities and sensibilities of the Chinese female writers in the 20th century and the imprints on love stories in their literary works. It starts with an overview of the development of autobiographic writing among the 20th century Chinese female writers, involving a number of stages with distinctive features respectively. More particularly, the poetics of "semi-autobiography" has increasingly prevailed since the 1990s. Drawing on feminist psychoanalysis and theories developed by J. Hillis Miller and Deuwe Fokklema, the subsequent chapters focus respectively on the autobiographic writings of Zhang Ailing, Qiong Yao, and San Mao in an effort to study the personalities of the female writers and their works.